2020
DOI: 10.2147/ott.s233149
|View full text |Cite
|
Sign up to set email alerts
|

<p>UPF1 Participates in the Progression of Endometrial Cancer by Inhibiting the Expression of lncRNA PVT1</p>

Abstract: Background: Endometrial carcinoma (EC) is the primary cause of death associated with cancer globally. Thus, the possible molecular mechanism of EC needs further exploration. Up-frameshift protein 1 (UPF1) is an ATPase depending on RNA/DNA and RNA helicase depending on ATP. Long noncoding RNA (lncRNA) plasmacytoma variant translocation 1 (PVT1) was dysregulated in diverse diseases. Methods: qRT-PCR and Western blot were applied to detect UPF1 and PVT1 in EC. CCK-8, colony formation, and Transwell assays were us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Thus, UPF1 is considered to mediate the degradation of the substrates of NMD via a phosphorylation/dephosphorylation cycle [ 38 , 39 ]. In tumorigenesis, recent investigations have demonstrated the inhibitory role of UPF1 in tumor progression in multiple cancers [ 40 – 42 ]. In HCC, UPF1 was demonstrated to act as a tumor suppressor via multiple pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, UPF1 is considered to mediate the degradation of the substrates of NMD via a phosphorylation/dephosphorylation cycle [ 38 , 39 ]. In tumorigenesis, recent investigations have demonstrated the inhibitory role of UPF1 in tumor progression in multiple cancers [ 40 – 42 ]. In HCC, UPF1 was demonstrated to act as a tumor suppressor via multiple pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Up‐frameshift protein 1 (UPF1) expressions were downregulated in EC tissues and cells and negatively correlated with lncRNA PVT1 expression levels. Furthermore, the downregulation of PVT1 was discovered to inhibit EC cell glycolysis 27 . Zhang et al 28 reported that an excess amount of SNHG16 lifted HK2 expression levels by sponging miR‐490‐3p, which subsequently promoted cell proliferation and glycolysis.…”
Section: Discussionmentioning
confidence: 99%
“…(D,E) Survival curves of NOL3 and UPF3B. *p < 0.05, **p < 0.01. endometrial carcinoma (Xing et al, 2020). UPF3A partially contributes to the effect of calcium homeostasis endoplasmic reticulum protein (CHERP) in promoting tumorigenesis in CRC (Wang Q. et al, 2019).…”
Section: Discussionmentioning
confidence: 99%